PKM Analisis Perhitungan Biaya Produksi Dalam Menetapkan Harga Jual Pada UMKM Mulyadi Shoes - Hannifah, Sul; Jasmadeti, Jasmadeti; Sutomo, Had (Jurnal Abdimas Dedikasi Kesatuan, 2021)
The role of micro, small, and medium-scale enterprises in the national economy is considerable, it should be expected to sustain it self at country, and it should compete in global markets. Company managers must be able to make the best decisions related to the increasing profits. The profit expected by the company depends one the calculating of the correct cost of production. The calculations of the cost of production are an important part of the company because it influences the selling price and profit a product. To avoid the errors that are occurring within calculating the underlying price of production and selling price requires the right method, the appropriate method used is the full costing method, because it takes into account all the elements of production cost, consisting of raw material costs, direct labor costs, and manufacturing overhead costs. The purpose of this study was to determine the calculation of production costs in determining the selling price. The author conducts research at UMKM Mulyadi Shoes located at Kampung Sindang Barang Desa Pasir Eurih, Kecamatan Taman Sari RT/01 RW/04. The techniques of data collection were interviews, observation, and literature studies. The method used in this study was a qualitative descriptive. The result of the study showed that based on the UMKM method, the cost of goods manufactured per unit was Rp 16.075,00. Whereas with the full costing method, the actual cost of production was Rp 16.337,00. The entrepreneur sets the selling price per unit was Rp 18.000,00. Whereas the selling price with the concept of total cost with the full costing method is as large was Rp 18.713,00. Then, it can be concluded that there was differences in the calculating of the production cost and the selling prices of the two methods. Therefore, it is better to calculate the cost of goods manufactured and the selling prices better using the full costing method, because using full costing methods his calculation whould be more accurate.   Keywords: Cost Of Goods Sold and Selling Price